2005
DOI: 10.1128/aem.71.7.3519-3523.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Incubation Temperature on Growth and Production of Exopolysaccharides by an Antarctic Sea Ice Bacterium Grown in Batch Culture

Abstract: The sea ice microbial community plays a key role in the productivity of the Southern Ocean. Exopolysaccharide (EPS) is a major component of the exopolymer secreted by many marine bacteria to enhance survival and is abundant in sea ice brine channels, but little is known about its function there. This study investigated the effects of temperature on EPS production in batch culture by CAM025, a marine bacterium isolated from sea ice sampled from the Southern Ocean. Previous studies have shown that CAM025 is a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
51
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(59 citation statements)
references
References 37 publications
7
51
0
1
Order By: Relevance
“…Many studies have shown the important role of EPS in buffering and cryoprotection for diverse microorganisms against ice crystal damage and high salinity (25,34,35). Cyanobacteria produce large amounts of EPS (24,36) and were the primary source of EPS genes in the mats from both Antarctica and the Arctic.…”
Section: Fig 3 Statistical Analyses Of Metabolic Profiles For the Arcmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have shown the important role of EPS in buffering and cryoprotection for diverse microorganisms against ice crystal damage and high salinity (25,34,35). Cyanobacteria produce large amounts of EPS (24,36) and were the primary source of EPS genes in the mats from both Antarctica and the Arctic.…”
Section: Fig 3 Statistical Analyses Of Metabolic Profiles For the Arcmentioning
confidence: 99%
“…Sulfate-reducing bacteria in the Deltaproteobacteria may also produce large amounts of EPS (5, 57). Nichols et al (34) showed that Proteobacteria (especially Gammaproteobacteria) and Bacteroidetes, which were common phyla in all three polar metagenomes, are able to synthesize EPS in response to low temperatures, implying that this is a cold-adaptation process.…”
Section: Fig 3 Statistical Analyses Of Metabolic Profiles For the Arcmentioning
confidence: 99%
See 1 more Smart Citation
“…The regenerated Fe can be immediately utilized by plankton or become trapped along with organic matter when sea-ice forms later in the season (Kepkay, 1994;Thomas et al, 2001;Lannuzel et al, 2007Lannuzel et al, ,2008Ackermann et al, 1994;Reimnitz et al, 1993;Sherwood, 2000;Smedsrud, 1998). This material, together with organic matter produced by the microbial community living within the sea-ice, are released the following season when the sea-ice melts (Lannuzel et al, 2010) and act as a source of dissolved ligands (Aguilar-Islas et al, 2008;Calace et al, 2001;Nichols et al, 2005;Pankowski and McMinn, 2008). Iron released from melting sea-ice may be pivotal for initiating the spring phytoplankton bloom, thanks to the presence of ligands that solubilize Fe.…”
Section: Phytoplankton Bloommentioning
confidence: 99%
“…The genome contains several putative genes connected with EPS production-22 predicted glycosyltransferases, several of which are located two genes downstream from putative UDP-N-acetylglucosamine 2-epimerases (epsC homologs) in eps gene cluster-like configurations (12,14). EPS production has been connected to psychrotolerance in several strains (1,6,8) and with increased pressure (6). The highest relative abundances of L. araneosa were measured in upper mesopelagic waters off the Oregon coast and at the Bermuda Atlantic Time Series station (2).…”
mentioning
confidence: 99%